Gestão do risco de crédito: análise dos impactos da resolução 2682, do conselho monetário nacional, na transparência do risco da carteira de empréstimo dos bancos comerciais brasileiros - Figueira, Paulo Humberto (2001)
This paper is aimed at carrying out a study of the classification methods for the Ioan portfoIio management and credit risk reported in the Iiterature concerned with credit, and the use of such instruments by BraziIian banks, as well as evaIuating the impact caused by ResoIution 2.682, dated 12/21/1999, upon such institutions' financiaI statements. That ResoIution estabIished that, as of march/2000, alI credit operations carried out by the financiaI institutions must be classified by a risk margin and that the clauses for inherent Iosses must be accounted for in face of their respective degree of risk. The probIem that is the object of this anaIysis is seen in a context in which the use by BraziIian financiaI institutions of tooIs to evaIuate credit risk has been enhanced for the reason that such part ofthe market, more competitive every day, has in credit a strategic instrument to Iever up proceeds. The use of methods for the classification of the Ioan portfoIio management and credit risk has a major premise to provide credit-granting institutions with an improvement in their decision process by alIowing them quickness, procedure standardizing, better instruments for quaIifying credit stafT, and costs reduction. It further aims at providing the market with the possibiIity of getting a deeper knowIedge of the Ioan portfoIio inherent risks, since the aforesaid ResoIution 2.682 ruIes that the financiaI institutions must detail their Ioan portfolio composition as of the reIeasing of their financiaI statements. The present study hypothesis is that such a regulation has contributed for the better evidencing ofthe loan portfolio risk in the financiai statements made public by financiai institutions.